An Innovative Multi-Story Trombe Wall as a Passive Cooling and Heating Technique in Hot Climate Regions: A Simulation-Optimization Study - Ahmed Abdelsamea; Hamdy Hassan; Hassan Shokry; Takashi Asawa; Hatem Mahmoud (Buildings)
This study develops an optimized multi-story Trombe Wall (MTW) as a hybrid passive system for heating, cooling, and PV electricity generation. Unlike previous research, which focused on single-story applications and heating efficiency, this study explores MTW performance in hot climates. The methodology includes four phases: identifying TW design parameters, selecting and validating a case study, applying a two-stage optimization, and developing predictive equations. Results show that the MTW achieves up to a 1.94 °C decrease in cooling mode, a 1.56 °C increase in heating mode, a 40% increase in thermal comfort hours, and a 31% rise in annual PV electricity generation. Finally, the developed regression models demonstrated strong predictive capability (R2 = 70.2–95.73%) for discomfort and electricity generation. The proposed MTW provides a cost-effective and sustainable solution, supporting designers and researchers in optimizing building performance.